USING PROTOTYPING METHOD FOR ANALYSIS AND DESIGN OF INFORMATION SYSTEMS FOR STUDENT REGISTRATION IN SEKOLAH MASTER - Lasminiasih Lasminiasih; Guntur Eka Saputra; Rooswhan Budhi Utomo; Elbi Wiseno (Asosiasi Dosen Muda Indonesia, 2022)
Sekolah Master or Master’s Schools is one of the schools for Education for equality of students for the less fortunate. One of the obstacles that master schools have is the absence of technology in student enrollment in schools. Many students wish to enroll and continue Education in masters schools to get an equivalency Education, so as to have the recognition of such Educational status. So far, schools are still using conventional methods in registration. Where, students and parents or families must come to school to register students or students by bringing the required documents, not to mention the requirements that cannot be completed, even queue time is needed to be served by the operator or staff on duty at the school. This shows that a technological device or system is needed to facilitate student enrollment in schools. One method that can be used to collect the required requirements and make a design is the prototyping method. The prototyping method is one of the methods used as an effort to develop a system with almost finished services and products. This method produces an analysis of functional and non-functional requirements that form the basis of the system that can be developed. This research also produced a design with a navigation structure, use case diagrams with a unified modeling language, relation tables, and interface proposals from end users and admins. This interface is used as a basis for the system to be made as a user-approved interface, so that the development of this system can be carried out properly during implementation and future trials.